Association between adhering to a dietary approach to stop hypertension and risk of colorectal cancer: a systematic review and meta-analysis - Mohammad Mehdi Abbasi; Paria Babaahmadi; Fateme Nozari; Farbod Khosravi; Zahra Golkar; Zahra Tavasoli; Venus Alizadeh; Marieh Nouriani; Mohammadsadegh Jafari; Niloufar Shabani; Hadis Hashemi Nezhad; Hossein Soltaninejad; et al. (BMC Gastroenterology)
Abstract Background Colorectal cancer (CRC) is a high incidence cancer and health problem influenced by many factors emphasizes on the importance of identifying risk factors which can be modified. A dietary approach to stop hypertension (DASH) style promotes a balanced nutrition approach that might have effects on CRC. The aim of this study was to analyze existing evidence on the DASH diet's association with CRC. Methods Databases, including Scopus, Web of Science, and PubMed, were searched to identify eligible studies up to March 2025. Observational studies investigating the association between adherence to the DASH diet and CRC were included. Effect sizes (ESs) and their confidence intervals (CIs) from fully adjusted models were extracted for the meta-analysis. A random-effects model was employed to calculate the combined ES and assess the relationship between the DASH diet and CRC. The publication bias was assessed using Egger’s test and heterogeneity between studies was examined using the I2 statistic. Results Fourteen studies were included in this study. Adherence to DASH diet reduced CRC risk (RR = 0.81, 95% CI: 0.73–0.89). Subgroup analyses found consistent effects across cohorts and various factors, with no publication bias. For rectal cancer (RC), adherence to DASH dietary pattern reduced risk of RC (RR = 0.75, 95% CI: 0.66–0.86), particularly in males and cohort studies. Colon cancer risk was also reduced (RR = 0.83, 95% CI: 0.79–0.88), with stronger effects in males and cohort studies. For colorectal adenoma, DASH showed a significant risk reduction (RR = 0.42, 95% CI: 0.22–0.80). Conclusions Our results highlight that following the DASH diet has a significant effect on lowering the risk of CRC which aligns with previous research. These findings support recommendation of following the DASH diet pattern reduces the burden of CRC. PROSPERO, registration ID: CRD42024569140.